Cultural context and characteristics of the institution as acculturation strategies - Martínez-Lara, Sandy Elizabeth; Tamez-González, Gerardo; Ganga-Contreras, Francisco Anibal (Política, Globalidad y Ciudadanía, 2021)
This article aims to determine the relationship between the cultural context and the characteristics of the institution as variables in the process of acculturation and cultural adaptarion in Higher Education students did an academic mobility abroad. Through a mixed methodology with qualitative and quantitative studies, through the use of semi-structured interviews applied to experts on issues of internationalization of Higher Education; likewise, a total of 43 surveys were applied to students who do an academic exchange during the years 2016-2017. The main results showed important relationships between the variables because the cultural context obtained a = .741, while characteristics of the institution a = .813. On the other hand, experts indicate that students should have as much previous knowledge about the culture and institution of the host country. This is how it is concluded that the cultural contex t and the characteristics of the institution are strategic factors within the acculturation process in students.